Effectiveness of mobile career competencies intervention for Malaysian public managers - Ho, Hsin Hung (2021)
Career competencies are competencies central to career development. Employees who master career competencies bring information, knowledge, and experience (working and learning) to the workplace, thus shaping their values and attitudes that contribute towards career success. However, there is a lack of career competencies practices in Malaysian public services. The study attempted to examine and support the Social Cognitive Career Theory (SCCT) in developing and delivering career intervention where lacking of evidence was significant. The study further extended SCCT in supporting career intervention delivery through mobile application. Therefore the study objective was to develop an efficient culture-specific mobile career competencies intervention in enhancing career competency among public servants in Malaysia, and subsequently to evaluate its effectiveness. This study is a sequential exploratory mixed-method design. Phase 1 (qualitative) developed a career competencies intervention protocol and explored the mobile application’s features preferred by the public manager. Phase 2 (quantitative) to validate and evaluate the Mobile Career Competencies Intervention (MCCI). In Phase 1- The career competencies intervention protocol was developed by combining and modifying features from CareerSKILLS Intervention, EPortfolio and Career Construction Intervention. The career competencies intervention protocol was then improvised through various consultations with an expert group in the career field and validated by senior career intervention experts by using Sidek’s Module Development Model and obtained an overall total of 86%. The protocol is suitable for the target group and meets the intervention module's targeted objective outcome. In the part 2 of the Phase 1, ten informants recruited to understand the reason using a mobile application, factor motivating, factor demotivating, and gamification elements are the themes to develop the MCCI. The outcomes from Phase 1 were transformed into mobile applications such as paper prototyping, personas, essential uses cases, and storyboard techniques. The mobile career competencies intervention was then developed using Android Studio 4.0 with Java Language Phase 2 - The MCCI obtained 82.87% on the usability score. The score showed that the MCCI perceived acceptable usability. Sixty-four participants (31 from intervention and 34 from the control group) out of 70 participants were included in the analysis for evaluation the MCCI purposes. The MCCI was effective in enhancing the overall career competencies with a mean difference of 0.283. The interaction effect is F(2,95)=6.574, p=0.005, η2=0.096. For the six sub career competencies, only four sub career competencies (reflection on motivation, reflection on qualities, work exploration, and career control) showed significant improvement. There is no significant difference on networking and self-profiling between the intervention and control group. The study concluded that the culture-specific mobile career competencies intervention effectively enhances career competency among public servants (manager) in Malaysia. Public managers can reflect on their motivation and qualities and proactively take action in their careers' learning and work processes.